THE INFLUENCE OF WORK DISCIPLINE AND COMPENSATION ON EMPLOYEE PERFORMANCE PT. DAEHAN GLOBAL SUKABUMI - Nurli Yanti; Dana Budiman (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2025)
This research aims to determine the effect of work discipline and compensation on employee performance at PT. Daehan Global Sukabumi. This research uses a quantitative approach with descriptive analysis. The population includes all 3,547 employees at the company. Using purposive sampling techniques, the sample was selected as 71 employees representing each department. Data was collected through a questionnaire which was measured on a 5 point Likert scale. Multiple linear regression analysis was used to analyze the data. The results of this research show that work discipline and compensation variables have a significant effect on the performance of PT employees. Daehan Global Sukabumi, and work discipline and compensation jointly influence the performance of PT employees. Daehan Global Sukabumi.